The Stage of Corporate Social Responsibility in EU-CEE Countries - Arraiano, Irene Guia; Hategan, Camelia Daniela (European Journal of Sustainable Development, 2019)
In the European Union, the importance of Corporate Social Responsibility reporting is increasing, because 2017 is the year in which the CSR reporting of large companies passes from the voluntary to the mandatory stage according to the requirements of the European Directive 2014/95/EU. In this context, this paper aims to examine the stage of Corporate Social Responsibility in Central and Eastern European Countries members of European Union, in accordance with Global Reporting Initiative which is consistent with globally recognised criteria worldwide, in the period 2002-2018. A critical analysis of the quality of the reporting was performed, looking at whether it has improved over the previous year and whether it respects legal requirements, and whether the communicated information is useful to the stakeholders. Base on literature review it was found that there is a gap of Corporate Social Responsibility’s reporting research to Western European countries. The results show that the evolution of reporting practices has improved over the years for the all countries and the most reports are prepared by multinationals companies. Thus, we can see how companies react to regulatory requirements and other government demands. Keywords: Corporate Social Responsibility, reporting, Global Reporting Initiative, Central and Eastern European Countries, quality